Islamic awakening and its role in Islamic solidarity in Egypt: contributions of the Muslim brotherhood - Abd Rahman, Saodah; Nurullah, Abu Sadat (International Islamic University Malaysia (IIUM), 2010)
Islamic revivalism led to the development of Islamic awakening throughout the Muslim world by uniting the Muslim society. In the process of liberating the Muslim countries from the colonists, all Muslims, including the traditionalists and secularists, felt the necessity of unity. Historically, Islamic awakening brought about the spirit of establishing principles of Islam in all affairs of the country, including the establishment of an Islamic state and the implementation of Islamic laws. In the case of Egypt, the Islamic awakening resulted in the emergence of three distinct Muslim groups, namely moderate Muslims, secularists, and radicals. This paper concentrates on the moderate Muslims, because in our view they are able to successfully incorporate Islamic principles at the grass root level. The Islamic organization, i.e. the Muslim Brotherhood (al-IkhwÉn al-MuslimËn), was established by the moderate Muslims and are actively involved in social services and charity activities.